Morphological Characterization of Some Fig Genotypes in the Jabal el-Sheikh Region - Damascus Governorate Using Some Morphological and Qualitative Characteristics (Damascus University Journal of agriculture sciences, 2026)
This research was carried out in the village of Harfa, located in the Jabal Al-Sheikh Region of the Rural Damascus Governorate-Syria, during the (2022/2023) grwon season. The research aimed to evaluate the morphological diversity of six fig types (Ficus carica L.) spread in the Jabal Al-Sheikh Region, (Saidawi Kabir, Saidawi Sagheer, Malaki, Khudairy, Halabloub, Aswad). The morphological Characteristics were read based on the fig descriptor approved by the International Plant Genetic Resources Institute (IPGRI), and the SPSS program was used to determine the degree of kinship and difference between these types, where the kinship tree was drawn on the basis of comparing all the studied morphological Characteristics and interrupting them with the types based on the presence (1) or absence (0) of Characteristic, and finding the Percent Disagreement Values (PDV). The study of morphological characteristics using eighteen morphological indicators related to the plant showed that there are a number of morphological characteristics that allowed the differentiation of types from each other, Three of the types (Khudairy, Saidawi Kabir, Saidawi Sagheer) gave secondary crop in addition to the main crop, Meanwhile, the rest of the types gave only the main crop. The UPGMA cluster analysis showed that the studied types were separated into two main groups. The first group included the two types (Sidawi Kabir and Saidawi Sagheer), which were closest to each other with a difference value of (1.414) and farthest from the rest of the types. Meanwhile, the second group was divided into three subgroups, the first subgroup included two types (Halabloub and Aswad), with a difference value of (3.317), whereas the two other subgroups included Malaki and Khudairi types.
Keywords: Fig, Ficus Carica L., Morphological characterization; Qualitative Characteristics.